1949
DOI: 10.1172/jci102218
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Balloon-Kymograph Recording of Intestinal Motility in Man With Observations on the Correlation of the Tracing Patterns With Barium Movements 1

Abstract: The balloon water manometer system has long been employed in animals and in man as a means of recording graphically the motility of the alimentary tract (1, 2). As others have done, we have used this method to study the behavior of adjacent segments of the small intestine in man under control conditions and in response to drugs and placebos (3, 4). The purpose of this communication is to describe the recording procedure and the evaluation of the tracing patterns. The results of the drug and placebo studies are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1952
1952
1983
1983

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The possibility of a connexion between the type lII waves and propulsion has received much attention. Some investigators using balloon and x-ray techniques have found a synchronism between the propulsion of the intestinal content and the occurrence of a type III wave (Chapman and Palazzo, 1949;Glazebrook, 1956). With the endoradiosonde technique we have not been able to confirm this view.…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of a connexion between the type lII waves and propulsion has received much attention. Some investigators using balloon and x-ray techniques have found a synchronism between the propulsion of the intestinal content and the occurrence of a type III wave (Chapman and Palazzo, 1949;Glazebrook, 1956). With the endoradiosonde technique we have not been able to confirm this view.…”
Section: Resultsmentioning
confidence: 99%
“…Their duration is 20-60 seconds, tending to the shorter period. They are due to peristaltic contractions and represent the passage of a single wave over the balloon (Chapman et al, 1949). They correspond with the "hunger contractions" of Carlson (1916) rig.…”
Section: Large Waves (L)mentioning
confidence: 99%